Selected Abstracts of the 20th National Congress of the Italian Society of Perinatal Medicine (Società Italiana di Medicina Perinatale, SIMP); Catania (Italy); March 22-24, 2018; Session "Perinatal infections" - - (Hygeia Press di Corridori Marinella, 2018)
20th National Congress of the Italian Society of Perinatal Medicine (Società Italiana di Medicina Perinatale, SIMP) Catania (Italy) • March 22nd-24th, 2018 SIMP PRESIDENT Irene Cetin CONGRESS PRESIDENTS Nicola Chianchiano, Angela Motta SCIENTIFIC COMMITTEE Mariarosaria Di Tommaso, Gianpaolo Donzelli, Luca Ramenghi ---------- Guest Editors: Irene Cetin, Nicola Chianchiano, Angela Motta ---------- Session "Perinatal infections" ABS 1. ROLE OF ABNORMAL CTG FEATURES IN CLINICAL AND SUBCLINICAL CHORIOAMNIONITIS • L. Galli, V. Whelehan, A. Archer, A. Dall'Asta, T. Frusca, E. Chandraharan ABS 2. HISTOLOGICAL CHORIOAMNIONITIS AT TERM: WHAT CLINICAL VALUE? • A. Pintucci, S. Consonni, L.E. Gioia, P. Colombo, P. Di Lorenzo, I. Vaglio Tessitore, F. Moltrasio, G. Bovo, A. Locatelli ABS 3. VALNOCTAMIDE RESCUES CYTOMEGALOVIRUS-INDUCED ABNORMAL BRAIN ONTOGENY AND DEAFNESS • S. Ornaghi, J. Bai, W. Tan, J. Santos-Sacchi, D. Navaratnam, A.N. van den Pol, M.J. Paidas, P. Vergani ABS 4. ZIKA TESTING IN PREGNANT AND PREGNANCY PLANNING WOMEN • G. Liuzzi, C. Castilletti E. Nicastri, F. Vairo, A. Corpolongo E. Lalle, M. Iannetta, L. Bordi, L. Scorzolini, F. Carletti, S. Quartu, F. Colavita, M.R. Capobianchi, G. Ippolito ABS 5. MEASLES IS AGAIN A PROBLEM • C.I. Palermo, C.M. Costanzo, R. Russo, M. Di Franco, G. Scalia ABS 6. OUTCOMES ASSOCIATED WITH FETAL PARVOVIRUS B19 INFECTION: A SYSTEMATIC REVIEW AND META-ANALYSIS • D. Buca, F. Bascietto, M. Liberati, D. Murgano, A. Iacovelli, M.E. Flacco, L. Manzoli, A. Familiari, G. Scambia, F. D'Antonio ABS 7. HIV INFECTION AMONG MIGRANT PEOPLE: A SINGLE CENTER EXPERIENCE • A. Giudicepietro, L. Sarno, G.M. Maruotti, L.L. Mazzarelli, M.C. De Angelis, A. Sirico, F. Zullo, P. Martinelli, M. Sansone ABS 8. FETAL PARVOVIRUS B19 INFECTION • V. Giardini, S. Lazzarin, A. Martinelli, S. Cozzolino, M. Verderio, P. Vergani ABS 9. MASTITIS AND BREAST ABSCESSES IN BREASTFEEDING: MILK CULTURE, ANTIBIOTIC TREATMENT AND FOLLOW UP • M.I. Mazzocco, P. Pileri, S.G. Rimoldi, A. Sartani, F. Romeri, S. Mancini, M.R. Gismondo, I. Cetin ABS 10. ACTIVE TUBERCULOSIS CASE-FINDING AMONG PREGNANT WOMEN PRESENTING TO AN OBSTETRICS CLINIC IN NORTHERN ITALY • M. Lamanna, V. Giardini, F. Sabbatini, P. Faverio, S. Lazzarin, P. Vergani ABS 11. LISTERIOSIS AND PREGNANCY: RESULTS FROM AN ITALIAN PILOT STUDY • L. Pucci, M. Massacesi, M. De Santi, G. Brandi ABS 12. INCIDENCE OF TOXOPLASMOSIS IN PREGNANCY: A POPULATION-BASED STUDY • V. Donadono, L. Sarno, A. Giudicepietro, L.L. Mazzarelli, G. Saccone, S. Tagliaferri, A. Sirico, G. Esposito, G.M. Maruotti, F. Zullo, P. Martinelli ABS 13. PARVOVIRUS B19 INFECTION IN PREGNANCY • V. Frisina, G. Masuelli, T. Todros ABS 14. PRETERM PREMATURE RUPTURE OF MEMBRANES (PPROM): CAN WE OPTIMIZE OUR FIRST LINE TREATMENT BY STUDYING THE LOCAL MICROBIOTA? • A. Dall'Asta, L. Angeli, E. Roletti, T. Ghi, T. Frusca ABS 15. PLACENTAL AND FETAL MEMBRANES INFECTION IN PREGNANCY WITH RUPTURE OF MEMBRANES. A PILOT STUDY • S. Cireddu, C. Gerosa, M. Anardu, F. Coghe, V. Fanos, G. Faa, S. Angioni